Clinical and immunological characteristics of TGM3 in pan-cancer: A potential prognostic biomarker - Zhang, Wenqing; Wu, Chenglong; Zhou, Kaili; Cao, Yu; Zhou, Wange; Zhang, Xue; Deng, Dan (Frontiers in Genetics, 2023)
Background: Recent studies have identified that transglutaminases (TGMs) are involved in a widespread epigenetic modification in tumorigenesis. However, it remains unclear how transglutaminase 3 (TGM3) affects in pan-cancer. The present study aimed to explore the clinical and prognostic function of TGM3 in pan-cancer as well as to explore the relationship of TGM3 expression with clinical stage, survival rate, prognosis condition, immune infiltration and mutation indicators. Methods: The relevant data of tumors were obtained from The Cancer Genome Atlas (TCGA), TARGET, Cancer Cell Line Encyclopedia (CCLE) and Genotype-Tissue Expression (GTEx) databases. According to the Human Protein Atlas (HPA) and TIMER databases, we evaluated the protein expression levels of TGM3 in different organs and tissues as well as their association with immune cell infiltration in pan-cancers. Expression differences between normal and tumor tissues as well as survival and prognosis situation, clinical data characteristics, tumor mutational burden (TMB), microsatellite instability (MSI), and RNA methylation were also assessed. Results: Compared to normal tissues, some tumor tissues had a lower expression level of TGM3, while other tumor tissues had a high expression level of TGM3. Further studies showed that high TGM3 expression had a certain risk impact on pan-cancer as high TGM3 expression levels were detrimental to the survival of several cancers, except for pancreatic cancer (PAAD). High expression level of TGM3 was also related to higher clinical stages in most cancers. The expression level of TGM3 was significantly negatively correlated with the expression of immune infiltration-related cells, including B cells, CD8+ T cells, CD4+ T cells, neutrophils, macrophages and dendritic cells (DCs). Furthermore, in most cancer types, TGM3 was inversely correlated with TMB, MSI, and methylation, suggesting that TGM3 expression can be used to assess potential therapeutic response, especially immune-related targeted therapy. Taken together, these bioinformatic analyses identified TGM3 as an important biomarker for clinical tumor prognosis and evaluation of treatment efficacy. Conclusions: We comprehensively analyzed the clinical characteristics, tumor stages, immune infiltration, methylation level, gene mutation, functional enrichment analysis and immunotherapeutic value of TGM3 in pan-cancer, providing implications for the function of TGM3 and its role in clinical treatment.